FDG-PET/CT で集積亢進を示した口底神経鞘腫の1例 - 宮崎, 晃亘; 清水, 翔太; 金子, 剛; 小池, 和茂; 平塚, 博義; 小林, 淳一 (日本口腔外科学会雑誌, 2018)
Schwannoma originate in the Schwann sheath of peripheral nerves; the incidence of schwannoma in the oral and maxillofacial region is low. We describe our experience with a patient who had a schwannoma that showed high uptake on a FDG-PET/CT scan. A 64-year-old woman underwent FDG-PET/CT imaging to evaluate primary lung cancer in depth. The scan demonstrated high uptake of FDG (SUVmax = 4.7) in the right side of the mouth floor, and the patient was therefore referred to our hospital. Echography and CT revealed an oval mass with smooth margins (diameter, 20 mm) in the vicinity of the sublingual gland in the right side of the mouth floor. Based on the clinical diagnosis, we resected the oral floor mass with the patient under general anesthesia in June 2015. In the intraoperative assessment, the tumor had a coat, but was contiguous with the lingual nerve and partly adhered to the sublingual gland. The histopathological diagnosis was schwannoma. On immunohistochemical staining, the tumor was GLUT-1 and GLUT-3 positive, suggesting that GLUT expression was involved in the high uptake of FDG. At 2 years of follow-up, we found no evidence of recurrence.